SUPEROVULATORY RESPONSE IN CROSSBRED COWS WITH MULTIPLE VERSUS SINGLE INJECTION OF FSH DISSOLVED IN POLYVINYLPYRROLIDONE - KARUNAKARAN, M; VEERAPANDIAN, C; SUBRAMANIAN, A; KATHIRESAN, D; DHALI, A; BHATT, B P; MANOKARAN, S (The Indian Journal of Animal Reproduction, 2023)
The use of a single FSH injection for inducing superovulation in cow is desirable. In this study we examined whether dissolving FSH in polyvinylpyrrolidone (PVP) would reduce the rate of absorption of FSH and allow it to be administered in a single dose for superovulation. Crossbred cows (n= 9 in each group) were superovulated either with a single intra-muscular injection of 18 mg FSH dissolved in 1 0 ml of 30 % PVP or with 18 mg of FSH dissolved in saline given as eight intra-muscular injections over four days period. Prostaglandin F 2alpha was given to all the cows 48 h after the first FSH injection. The cows were inseminated with frozen semen at 12 and 24 h following the estrus onset. Superovulatory response was assessed by palpation per rectum on day 7 post breeding and the cows with more than 2 corpus luteum (CL) were flushed. Progesterone level in the blood samples collected on the day of first FSH injection and on the day of embryo collection were found to be significantly (P<0.05) higher in multiple injection group (7.3 ± 1.4 and 22.6 ± 4.6 ng/ml) compared to the single injection group (2. 77 ± 1.15 and 10.9 ± 3.3 ng/ml). Nevertheless the number of transferable embryos in multiple injection group (1.9 ± 0.8) and single injection group (1.0 ± 0.8) did not differ significantly. The study revealed that 18 mg of FSH was not sufficient to induce satisfactory superovulation in crossbred cows through the single PVPFSH injection protocol or conventional multiple FSH injections protocol.